CONSTRUSTIVISTIC BIOLOGY INSTRUCTIONAL MODEL ICT-BASED (CBIM-ICT-BASED) FOR JUNIOR HIGH SCHOOL STUDENTS - ., adnan (Journal of Educational Science and Technology, 2015)
ABSTRACTThis research aimsÂ  to develop a model of ICT-based contrustivistic biology learning (CBL-based ICT) for Junior High School students were valid. The problem posed is "What is CBL-based ICT model were developed refer to the theory and its constituent components?. The research subjects were students of Junior High School 6 Makassar, Indonesia. Procedures development of CBL-based ICT was implemented refer to development model of Plomp (1997) which consists of five stages, such as (1) preliminary investigation, (2) design, (3) realization/construction, (4) testing, evaluation and revision, and (5) implementation. Research product is CBL-based ICT. Component model were developed refer to Joyce, et al. (1992). The characteristic of the model were developed refer to Arend (2012), and the criteria for product quality refer to Nieeven (2007). Data analysis of validity refers to Nurdin (2007) and Hobri (2009). The percentage of instruments reliability was used the percentage agreements concept by Grinnell 1988 (in Hobri 2009). The results showed that CBL-based ICT developed were valid referred by constituent theory and component support model.Â Keyword: MPBK-based ICT, constructivism, blended learning, e-learning